A Meta-Analysis of Osteosarcoma Outcomes in the Modern Medical Era. (18th March 2012) - Allison, Daniel C.; Carney, Scott C.; Ahlmann, Elke R.; Hendifar, Andrew; Chawla, Sant; Fedenko, Alex; Angeles, Constance; Menendez, Lawrence R.
Abstract : Four decades ago, specialized chemotherapy regimens turned osteosarcoma, once considered a uniformly fatal disease, into a disease in which a majority of patients survive. Though significant survival gains were made from the 1960s to the 1980s, further outcome improvements appear to have plateaued. This study aims to comprehensively review all significant, published data regarding osteosarcoma and outcome in the modern medical era in order to gauge treatment progress. Our results indicate that published survival improved dramatically from 1960s to 1980s and then leveled, or in some measures decreased. Recurrence rates decreased in the 1970s and then leveled. In contrast, published limb salvage rates have increased significantly every recent decade until the present. Though significant gains have been made in the past, no improvement in published osteosarcoma survival has been seen since 1980, highlighting the importance of a new strategy in the systemic management of this still very lethal condition.